Out-of-pocket medical expenditures, remittances and health outcomes in China - Li H.; Zhang X.; Ma F.; Osabohien R. (Women's Health and Action Research Centre, 2025)
This study examines the relationship between out-of-pocket medical expenditures, remittances and health outcomes in China using Ordinary Least Squares (OLS) and Propensity Score Matching (PSM) methods. The analysis is based on data from the Global Financial Inclusion database by the World Bank (2021), encompassing a sample of 3,446 individuals. The results indicate that out-of-pocket expenditure has a negative impact on health outcomes, while remittance shows a positive association across all age groups, including reproductive and non-reproductive populations. These findings suggest that high out-of-pocket medical costs may hinder access to healthcare services and lead to poorer health outcomes. Conversely, remittance plays a beneficial role in improving health outcomes, highlighting the potential of financial support to positively impact the well-being of individuals. (Afr J Reprod Health 2024; 28 [8]: 122-132). ? 2024, Women's Health and Action Research Centre. All rights reserved.